2011
DOI: 10.1002/aic.12636
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of oxide and vanadate supports for catalytic hydrogen combustion: Kinetic and mechanistic investigations

Abstract: ) were tested for catalytic hydrogen combustion. The compounds were characterized by X-ray diffraction and X-ray photoelectron spectroscopy. All the four compounds showed good activity and stability for catalytic hydrogen combustion and more than 95% conversion was observed over all the compounds within 500 C. The mechanisms for the reaction over the different classes of compounds (cerium-based and iron-based compounds) were proposed on the basis of spectroscopic observations. The main difference in the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…FeVO 4 is widely applied in high energy density lithium batteries [7], photocatalysts [8], catalytic hydrogen combustion [9]. Recently, M. Casanova and coworkers [10] firstly found that FeVO 4 /TiO 2 -WO 3 -SiO 2 catalysts showed high catalytic activity in the NH 3 -SCR reaction at 250-450°C.…”
Section: Introductionmentioning
confidence: 99%
“…FeVO 4 is widely applied in high energy density lithium batteries [7], photocatalysts [8], catalytic hydrogen combustion [9]. Recently, M. Casanova and coworkers [10] firstly found that FeVO 4 /TiO 2 -WO 3 -SiO 2 catalysts showed high catalytic activity in the NH 3 -SCR reaction at 250-450°C.…”
Section: Introductionmentioning
confidence: 99%
“…One of the primary functions of the catalysts is to facilitate dissociation of the H 2 molecule by weakening the H-H bond through adsorption onto the catalyst surface. And the results of hydrogen catalytic combustion indicated that this monolithic catalyst had high activity for hydrogen combustion reaction, which could quickly start up even at 263 K. For low temperature catalytic combustion of 4 , and FeVO 4 ) as support on catalytic hydrogen combustion [14]. For example, an earlier experimental study has examined the effect of fundamental conditions of hydrogen-fueled catalytic burners on their operating properties [12].…”
Section: Catalytic Combustionmentioning
confidence: 99%
“…Source: Reproduced with permission from Deshpande et al[14]. Source: Reproduced with permission from Deshpande et al[14].…”
mentioning
confidence: 99%
“…In order to ensure the stability of the catalyst, experiments were conducted similar to our previous study. 22 The oxidation of CO was carried out continuously for 4 h over the samples at 450 1C and the spectra of the spent catalyst were recorded. Both the XRD and XPS spectra of the catalysts did not show any large change in the oxidation state indicating the stability of the materials.…”
Section: Co Oxidation Experimentsmentioning
confidence: 99%
“…Diffusion of Ce 3+ ions into Al 2 O 3 from the reduction of CeO 2 is possible only at high temperatures. 22 However, cation substitution in CeO 2 is possible and has been reported by several techniques. [27][28][29] We have previously reported the use of the solution combustion technique for the synthesis of solid solutions of CeO 2 with TiO 2 , ZrO 2 and SnO 2 .…”
Section: Synthesismentioning
confidence: 99%